The Positive Impact of Group Counseling for the Management of the Islamic Youth Mosque Organization - Ristianti, Dina Hajja (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to explain the positive impact of group counseling on the management of youth mosque organizations at the Risma Al-Huda Mosque, Panorama Village, Bengkulu City. This research is qualitative with a case study approach; the source of research data is ten people who are members of groups/counseling groups, the object of research is carried out at the Risma Al-Huda mosque, Panorama District, Bengkulu City, and data collection is carried out by interview, observation, and documentation techniques, data analysis techniques by data reduction, data presentation, and conclusion drawing. The study concluded that group counseling could provide significant benefits for organizational management. Based on group counseling activities in Risma Al-Huda, Panorama District, Bengkulu City, it was found that groups establish interaction between group members, which can improve communication and cooperation between them. Members of Risma Al-Huda, Panorama Sub-district of Bengkulu City, learn to observe with empathy, share thoughts, and work together to achieve common goals. Communication and cooperation skills acquired in group counseling can be applied in the work area, helping to build strong team bonds and improve organizational performance. So it can be concluded that group guidance can have a good impact on youth mosque management; for example, it can improve communication, cooperation, problem-solving, community welfare, and skill development, so group guidance must continue to be developed.